Yuna Gloves, Sarung Tangan Anti Carpal Tunnel Syndrome (CTS) Pada Ibu Hamil - Rif'atul Mahmudah; Sri Wulan Sindiawati; Nina Agustina; Siti Nurhayati; Siti Jamiami (Jurnal Obstretika Scientia, 2022)
Carpal Tunnel Syndrome (CTS) is a symptom of compression neuropathy of the median nerve at the wrist. Characterized by increassed pressure in the carpal tunnel and decreased nerve function. The Most Common Complain are pain, numbness and tingling along the distribution of the median nerve. The prevalence of carpal tunel syndrome in the adult population ranges from 0.7 – 9.2%, 0.4% in women and 2.1% in men. Women have a riskof developing CTS 3 times higher in pregnant women then in non-pregnant women. The purpose of this study was tu produce yuna gloves which were effective in reducing the incidence of CTS in pregnant women at the Cipanas Health Center in 2021. This study was conducted using the case control method, which is to campare existing Products with research products. This researche process lasted for 3 months. The population in this study were all pregnant women in the third trimester at the Cipanas Public Health, which amaunted to 150 people, the sample in this study amounted 33 people. From the results of the case study, its expected to further improve the quality of service delivery for health workers, aspecially in handling cases of CTS in pregnant women at the Cipanas Health Center.